Investigation of reverse ionic diffusion in forward-osmosis-aided dewatering of microalgae: A molecular dynamics study. (May 2019) - Itliong, Jester N.; Villagracia, Al Rey C.; Moreno, Joaquin Lorenzo V.; Rojas, Kurt Irvin M.; Bernardo, Gian Paolo O.; David, Melanie Y.; Manrique, Robby B.; Ubando, Aristotle T.; Culaba, Alvin B.; Padama, Allan Abraham B.; Ong, Hui Lin; Chang, Jo-Shu; et al.
Highlights: Higher draw solution concentration led to lower diffusion coefficients of ions. Higher draw solution concentration induced lower hydration numbers of ions. The ionic permeability and hydration number of cations are inversely proportional. Mg 2+ ions resulted to lower ionic permeability as compared to Na + ions. Ions permeate the membrane as pairs although they exist individually in solution. Abstract: This study aimed to investigate the transport mechanisms of ions during forward-osmosis-driven (FO-driven) dewatering of microalgae using molecular dynamics (MD) simulations. The dynamical and structural properties of ions in FO systems of varying NaCl or MgCl2 draw solution (DS) concentrations were calculated and correlated. Results indicate that FO systems with higher DS concentration caused ions to have lower hydration numbers and higher coordination numbers leading to lower diffusion coefficients. The higher hydration number of Mg 2+ ions resulted in significantly lower ionic permeability as compared to Na + ions at all concentrations ( p = 0.002). The simulations also revealed that higher DS concentrations led to higher accumulation of ions in the membrane. This study provides insights on the proper selection of DS for FO systems.